Perancangan Dan Pembuatan Alat Penekan Piston Rem Sepeda Motor - Muh Anhar Anhar; Fickry Ghusti Febryan; Asep Ruchiyat; Hairian Rahmadi; Yudhi Chandra Dwiaji (Pengelola Jurnal Politeknik Negeri Ketapang, 2026)
Because many mechanics in general repair shops still press brake pistons using a ring spanner, which often causes the brake pistons to be scratched or broken, the purpose of this study is to assist mechanics in the brake pad installation process to avoid piston damage and to understand how the brake piston presser works.The methods used include literature review, field observation, design using AutoCAD software, and the manufacturing process, which consists of four main stages: material preparation (iron plate, bolts, nuts). After the tool is completed, testing is conducted to ensure its function and efficiency. The average time for the brake piston presser tool is 06.47 seconds, while the average time when using a ring spanner is 07.72 seconds. The test results can be seen from the efficiency of the brake piston presser tool made by the author